The effects of CeO2 addition on the physical and microstructural properties of ZTA-TiO2 ceramics composite - Ahmad Azhar, Ahmad Zahirani; Mohamad Shawal, Siti Hajar; Manshor, Hanisah; Mohd Ali, Afifah; Rejab, Nik Akmar; Chan Abdullah, Ezzat; Ahmad, Zainal Arifin (Elsevier, 2019)
The effect of CeO2 addition ranging from 0 wt. % to 7 wt. % on phase, microstructural evolution, physical and mechanical properties of ZTA-3 wt. % TiO2 ceramic composite were investigated. The samples were prepared by solid-state mixing and sintered at 1600 °C for 1hr under pressureless condition. Samples were then characterized by XRD, SEM, densitometer and Vickers indentation method. Based on XRD analysis, m-ZrO2 began to diminish at 1 wt.% CeO2 while secondary phases, i.e. Ce0.7Zr0.3O2and Zr0.4Ti0.6O2 initiated at 3 wt.% CeO2 addition. SEM images showed finer grain sizes was produced upon increasing amount of CeO2 up to 5 wt.%, corresponding to higher average grain intercept (AGI) values. From the results obtained, the optimum amount of CeO2 addition was at 5 wt. % which yielded the highest bulk density (4.41 g/cm3), firing shrinkage (21.94%), hardness (1580.10HV) and fracture toughness (9.77 MPa m1/2). This is contributed by the grain refinement and the highest amount of secondary phases formed, especially Zr0.4Ti0.6O2. However, with an excessive addition of CeO2, i.e more than 5 wt.%, grain sizes enlarged and the amount of secondary phases reduced, which degraded the mechanical properties of ZTA-3 wt. % TiO2.